Moving With Invisible Disability, Sentient Bodies Of Women With Visceral Deficiencies In Chilean Patagonia - Solsona-Cisternas, Diego; Acuna-Oyarzun, Belen; Nunez-Mansilla, Karen (My University, 2021)
This research presents the results of a qualitative study an ethnographic design, to comprehensively approach the mobility experiences of a group of women with various medical diagnoses in Chilean Patagonia, by the way, experiences embedded in more complex frames of social life such as the disability. Through mobile ethnographies and interviews, we were able to observe their mobility practices emphasizing the sensations and meanings of these, mediated by bodies that carry a disability. The results suggest that these women with visceral disabilities practice differentiated mobility characterized by slowness, body discomfort, fear, loss of spatial orientation, in some cases the avoidance of displacements. In addition to deploying strategies to overcome obstacles to move and recognition. Also emphasizing the fatigue and social suffering of invisible bodies that are thrown into public space.
Keywords: Visceral Disability; Mobility; Bodies/Emotions; Mobile Ethnographies